Perlindungan Hukum Bagi Korban Perundungan Di Lingkungan Pendidikan - Maria Theresia Avila Nia; Hendrika Nio Do Beke; Maria Theresia Wona; Maria Emmanuela Lebo; Maria Bergita Bhoko; Aplonia kua; Ririnsia Anjelin Go'o; Kornelia Rima Demo; Ludifika Claudia Owa; Hildegardis Ule (Jurnal Inovasi Pendidikan Dan Pembelajaran, 2026)
The educational environment should be a safe space to shape the character and morals of students. However, the increase in cases of bullying in schools shows that there is an imbalance in power relations that triggers systematic violence. This research aims to analyze the effectiveness of Indonesian positive law in providing protection for victims of bullying and examine the gap between legal rules and practice in the field. The research method used is juridical-empirical with a document study approach to laws and regulations and analysis of mass media news related to bullying cases in Indonesia for the 2020–2026 period. The research results show a significant increase in cases of violence in educational units and a predominance of male victims. Apart from that, it was found that schools tend to carry out pseudo-mediation in order to maintain their reputation, thereby neglecting the recovery of victims. Handling bullying is still weak in terms of legal implementation and internal supervision. Therefore, a victim-oriented approach is needed, strengthening TPPK, as well as a safe and responsive reporting system